Hematopoeitic Cell Transplantation and CAR T-Cell Therapy: Complements or Competitors? - Goldsmith, Scott R.; Ghobadi, Armin; DiPersio, John F. (Frontiers in Oncology, 2020)
Allogeneic hematopoietic cell transplantation (allo-HCT) and chimeric antigen receptor T cell (CAR T) therapy are the main modalities of adoptive cellular immunotherapy that have widely permeated the clinical space. The advent of both technologies revolutionized treatment of many hematologic malignancies, both offering the chance at sustained remissions for patients who would otherwise invariably succumb to their diseases. The understanding and exploitation of the nonspecific alloreactivity of allo-HCT and the graft-versus-tumor effect is contrasted by the genetically engineered precision of CAR T therapy. Historically, those with relapsed and refractory hematologic malignancies have often been considered for allo-HCT, although outcomes vary dramatically and are associated with potential acute and chronic toxicities. Such patients, mainly with B-lymphoid malignancies, may now be offered CAR T therapy. Yet, a lack of prospective data to guide decisions thereafter requires individualized approaches on whether to proceed to allo-HCT or observe. The continued innovations to make CAR T therapy more effective and accessible will continue to alter such approaches, but the similar innovations in allo-HCT will likely results in similarly improved clinical outcomes. In this review we describe the history of the two platforms, dissect the clinical indications emphasizing their intertwining and competitive roles described in trials and practice guidelines, and highlight innovations in which they complement or inform one another.